Probing the membrane interface-interacting proteome using photoactivatable lipid cross-linkers. - Gubbens, J; Vader, P; Damen, J; O'Flaherty, M; Slijper, M; de Kruijff, B; de Kroon, A (2007)
To analyze proteins interacting at the membrane interface, a phospholipid analogue was used with a photoactivatable headgroup (ASA-DLPE, N-(4-azidosalicylamidyl)-1,2-dilauroyl-sn-glycero-3-phosphoethanolamine) for selective cross-linking. The peripheral membrane protein cytochrome c from the inner mitochondrial membrane was rendered carbonate wash-resistant by cross-linking to ASA-DLPE in a model membrane system, validating our approach. Cross-link products of cytochrome c and its precursor apocytochrome c were demonstrated by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and were specifically detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), taking advantage of the intrinsic UV absorbance of the cross-linker. Application of the method to inner mitochondrial membranes from Saccharomyces cerevisae revealed cross-link products of both exogenously added apocytochrome c and endogenous proteins with molecular weights around 34 and 72 kDa. Liquid chromatograpy (LC)-MS/MS was performed to identify these proteins, resulting in a list of candidate proteins potentially cross-linked at the membrane interface. The approach described here provides methodology for capturing phospholipid-protein interactions in their native environment of the biomembrane using modern proteomics techniques.